Compliance Bargaining Mechanism as The Way to Ended Iran-Iraq War 1988 - Aditya Maulana Hasymi (President University, 2020)
AbstrakIsu-isu terkait budaya, ekonomi, dan nilai seringkali menghasilkan konflik. Tak terkecuali dengan isu perebutan wilayah. Salahsatu perang terbesar yang terkait dengan isu sengketa wilayah adalah perang Iran-Irak 1988. Perang Iran-Irak 1988 membawa sejarah besar dari kedua negara yang saling berhubungan dengan isu perebutan wilayah, perebutan pengaruh ideologi, dan isu ekonomi. Perang yang berlangsung cukup lama ini membuat Iran dan Irak menyadari akan kerugian jangka panjang yang dialami. Pada akhirnya, kedua negara sepakat untuk berdamai dalam sebuah proses yang melibatkan pihak ketiga. Perserikatan Bangsa-Bangsa mengambil peran sebagai pihak ketiga yang membantu penyelesaian perang antara Iran dan Irak. Resolusi no.598 yang disusun oleh Perserikatan Bangsa-Bangsa mengarisbawahi akan pentingnya gencatan senjata dengan banyaknya kerugian dan korban jiwa yang muncul. Penelitian ini berargumen bahwa upaya Perserikatan Bangsa-Bangsa menyusun resolusi no.598 dalam menyelesaikan perang Iran-Irak adalah penerapan dari mekanisme compliance bargaining pada proses resolusi konflik.Kata kunci: compliance bargaining, resolusi konflik, rezim, gencatan senjata AbstractConflictual issues can be about economy, culture and values, or even a border dispute. The class cannot be avoided because of several issues triggering the conflict and also several interests. One of the bigger wars that can be was the Iran-Iraq War at 1980-1988. This war brought the long history between both of those countries, which were related with border disputes, ideological influences, and economic war. Those of both countries is thinking that if the war is still being run, it is not giving any good advantage. The damage was so big. So, it required a process to bring the two states involved war into one meeting to talk about peace or end the war. The process is called a peace process. In this case, the peace process arranged by the involvement of third party. The United Nations take a role as the third party in Iran-Iraq War by formed a Resolution no 598. In the resolution the council expressed its concern that, despite its calls for ceasefire, the conflict between Iran and Iraq continued with heavy loss of life and material destruction. The Iran-Iraq war was ended through the resolution no 598 that was produced by the United Nations. Furthermore, this paper argue that the way of the United Nations ended the Iran-Iraq war through Resolution no 598 is implementing the theory of compliance bargaining in conflict resolution.Keywords: compliance bargaining, conflict resolution, regime, ceasefire